Juegos lúdicos y desarrollo psicomotriz en niños de la Institución Educativa Inicial N° 728 del distrito de Ramón Castilla 2023 - Falcon Sanchez, Sandra Milena (2024)
The objective of this research was to determine the relationship between recreational games and the psychomotor development of children from IEI 728 in the Ramón Castilla district, during the 2023 school year. A quantitative, relational, non-experimental, transectional and correlational methodology was used. . The study population and sample consisted of 60 parents, to whom two questionnaires were administered to collect information. The inferential analysis, carried out using Spearman's correlation, yielded a correlation coefficient of 0.928 with a p-value of 0.000, confirming a very high positive relationship between recreational games and the psychomotor development of children.